Federal Court Cases: Integrated Data Base Bankruptcy Petitions, 2012 ([Verlag nicht ermittelbar], 2016)
In 2008, the Administrative Office of the United States Courts (AOUSC) began implementing the NewSTATS (New Streamline Timely Access to Statistics) Project with respect to bankruptcy data. The project's goals were to modernize the system for collecting, processing, analyzing, and reporting statistics of the federal court system. Based on the records for bankruptcy cases in NewSTATS, a data base for internal use in the Research Division of the Federal Judicial Center has been created. That data base is the Bankruptcy Petition NewSTATS Snapshots [BPNS] Data Base.